ANOMALI REFORMASI PENYELENGGARAAN PEMBELAJARAN DI INDONESIA - M. Yusuf T. M. Yusuf T. (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2012)
Abstract: Reform is layered changes that led to the creation of new designs for an order. Educational settings are vital nation order that has not yet reached full reform implementation even if the notice had anomalous orientation after UUSPN endorsed national education. If you listened to, the national educational regulations have changed the paradigm of national learning paradigm to paradigm constructivism forming behavior. Translation is a new way of organizing learning into practice is not easy, requiring a comprehensive conceptual transformation boils down to the micro sector of education, namely the class. The argument is simple, the quality of learning in the classroom indicate the quality of the education system as a whole.Abstrak: Reformasi adalah perubahan berlapis yang berujung pada penciptaan desain baru atas suatu tatanan. Tatanan pendidikan adalah tatanan sangat vital berbangsa yang belum mencapai reformasi utuh bahkan mengalami anomali penyelenggaraan jika memperhatikan orientasi pendidikan nasional setelah UUSPN disahkan. Jika disimak, regulasi pendidikan nasional tersebut telah mengubah paradigma pembelajaran nasional dari paradigma pembentukan perilaku kepada paradigma konstruktifistik. Terjemahan cara baru tersebut ke dalam praktek penyelenggaraan pembelajaran tidaklah mudah, membutuhkan transformasi konseptual yang secara komprehensif bermuara pada sektor mikro pendidikan, yaitu kelas. Argumennya sederhana, kualitas pembelajaran di kelas mengindikasikan kualitas sistem pendidikan secara menyeluruh.